Temporal β diversity—A macroecological perspective. Issue 12 (10th November 2019) - Magurran, Anne E.; Dornelas, Maria; Moyes, Faye; Henderson, Peter A.
Abstract: Issue: Biodiversity change, that is how the taxonomic identities and abundances of species in ecological systems are changing over time, has two facets: temporal α diversity and temporal β diversity. To date, temporal α diversity has received most attention even though compositional shifts in assemblages exceed expectations based on ecological theory. Growing concern about the state of the world's biodiversity highlights the need for better understanding of the extent, and consequences, of compositional reorganization in ecological systems. Challenges: Most methods of measuring β diversity have been developed in a spatial context. We discuss the additional challenges involved in the assessment of temporal change, summarize existing methodological approaches, highlight the importance of establishing relevant baselines, and identify the need for appropriate null models of temporal β diversity. Given considerable potential for research on the macroecology of temporal β diversity we suggest future directions and challenges. Conclusions: Although data availability remains the main impediment to improved quantification of temporal β diversity at macroecological scales, there are substantial opportunities for improved methodology and theory. Taxonomic β diversity has received most attention, but other dimensions of diversity, including functional and phylogenetic, should be part of integrated assessments of biodiversity change. Future approaches need to be ecologically meaningful and interpretable as well as statistically robust.